Effects of β-alanine supplementation during a 5-week strength training program: a randomized, controlled study - José Luis Maté-Muñoz; Juan H. Lougedo; Manuel V. Garnacho-Castaño; Pablo Veiga-Herreros; María del Carmen Lozano-Estevan; Pablo García-Fernández; Fernando de Jesús; Jesús Guodemar-Pérez; Alejandro F. San Juan; Raúl Domínguez (Taylor & Francis Group, 2018)
Background β-Alanine (BA) is a non-essential amino acid that has been shown to enhance exercise performance. The purpose of this investigation was to determine if BA supplementation improved the adaptive response to five weeks of a resistance training program. Methods Thirty healthy, strength-trained individuals were randomly assigned to the experimental groups placebo (PLA) or BA. Over 5 weeks of strength training, subjects in BA took 6.4 g/day of BA as 8 × 800 mg doses each at least 1.5 h apart. The training program consisted of 3 sessions per week in which three different leg exercises were conducted as a circuit (back squat, barbell step ups and loaded jumping lunges). The program started with 3 sets of 40 s of work per exercise and rest periods between sets of 120 s in the first week. This training volume was then gradually built up to 5 sets of 20 s work/60 s rest in the fifth week. The work load during the program was set by one of the authors according to the individual's perceived effort the previous week. The variables measured were average velocity, peak velocity, average power, peak power, and load in kg in a back squat, incremental load, one-repetition maximum (1RM) test. In addition, during the rest period, jump ability (jump height and power) was assessed on a force platform. To compare data, a general linear model with repeated measures two-way analysis of variance was used. Results Significantly greater training improvements were observed in the BA group versus PLA group (p = 0.045) in the variables average power at 1RM (BA: 42.65%, 95% CI, 432.33, 522.52 VS. PLA: 21.07%, 95% CI, 384.77, 482.19) and average power at maximum power output (p = 0.037) (BA: 20.17%, 95% CI, 637.82, 751.90 VS. PLA; 10.74%, 95% CI, 628.31, 751.53). The pre- to post training average power gain produced at 1RM in BA could be explained by a greater maximal strength gain, or load lifted at 1RM (p = 0.014) (24 kg, 95% CI, 19.45, 28.41 VS. 16 kg, 95% CI, 10.58, 20.25) and in the number of sets executed (p = 0.025) in the incremental load test (BA: 2.79 sets, 95% CI, 2.08, 3.49 VS. PLA: 1.58 sets, 95% CI, 0.82, 2.34). Conclusions β-Alanine supplementation was effective at increasing power output when lifting loads equivalent to the individual's maximal strength or when working at maximum power output. The improvement observed at 1RM was explained by a greater load lifted, or strength gain, in response to training in the participants who took this supplement.